On a generalization of the seating couples problem - Kohen, Daniel (2016)
We prove a conjecture of Adamaszek generalizing the seating couples problem to the case of 2n seats. Concretely, we prove that given a positive integer n and d1,…,dn∈(Z/2n)× we can partition Z/2n into n pairs with differences d1,…,dn.